1992
DOI: 10.1002/mc.2940050107
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transforming growth factor‐alpha in regenerating liver and during hepatic differentiation

Abstract: Both the level of expression and cellular distribution of transcripts for transforming growth factor-alpha (TGF-alpha) were studied in adult rat liver after partial hepatectomy and during hepatic differentiation in fetal, neonatal, and adult livers by northern blot analysis and in situ hybridization. A marked increase in the expression of TGF-alpha was observed in neonatal livers and in adult livers after partial hepatectomy and during hepatic regeneration following modification of the Solt-Farber protocol. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 22 publications
0
65
0
1
Order By: Relevance
“…In both the intact adult and weanling livers, as well as in freshly isolated cell subpopulations, the principal concentration of ALR peptide and essentially all of the mRNA transcripts were in hepatocytes, similar to TGF-␣ 34,35 but unlike the hepatotrophic HGF 37 and antihepatotrophic TGF-␤ 46,47 that are synthesized by NPCs (Table 1). ALR also was found by immunolabeling in the NPCs of the intact livers, but the peptide was irregularly distributed and of lower concentration than in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In both the intact adult and weanling livers, as well as in freshly isolated cell subpopulations, the principal concentration of ALR peptide and essentially all of the mRNA transcripts were in hepatocytes, similar to TGF-␣ 34,35 but unlike the hepatotrophic HGF 37 and antihepatotrophic TGF-␤ 46,47 that are synthesized by NPCs (Table 1). ALR also was found by immunolabeling in the NPCs of the intact livers, but the peptide was irregularly distributed and of lower concentration than in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…60 A marked increase in hepatic aFGF levels has been reported at the peak of oval cell proliferation in the 2-AAF/PH model, and levels greatly exceeded those observed after PH alone, suggesting a more prominent role for aFGF in oval cellmediated regeneration. 54 High levels of TGF-a expression are observed not only in hepatic stellate cells, but also in oval cells in the 2-AAF/PH model, 50,61 and TGFa expression is detected in foci of hepatocytes that appear to be oval cell-derived. Similar results have been observed in human hepatitis B-associated HCC, where TGF-a is localized to oval cells.…”
Section: Role Of Hepatic Stellate Cellsmentioning
confidence: 99%
“…The fact that infusion of TGF-α increases oval cell proliferation after 2-AAF/PH protocol [15] suggested that EGFR signalling is also an important regulator of liver progenitor cells proliferation in a regenerative context, but for now, the impact of deleting EGFR signalling in liver regeneration from oval progenitor cells remains undefined. Interestingly, TGF-α transcripts are undetectable or very low in normal liver or non-replicating hepatocytes, but are up-regulated in hepatocytes during partial hepatectomy and toxic injury [32,33] as well as in proliferating oval cells and basophilic foci of hepatocytes in regenerating liver induced by a modified Solt-Farber protocol [12], providing indirect evidence for the implication of an autocrine mechanism. Here, using in vitro approaches we present the first direct evidence of the autocrine action of EGFR ligands in non-tumorigenic oval cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both TGF-α and HGF, as well as their respective receptors, ErbB1 and c-Met, are transcriptionally up-regulated during the period of active proliferation and differentiation of progenitor cells in the rat liver subjected to the 2-acetylaminofluorene/partial hepatectomy (2-AAF/PH) protocol [12][13][14]. Furthermore, in vivo infusion with either EGF or HGF amplifies liver progenitor expansion following liver injury and decreases cell apoptosis [15].…”
Section: Introductionmentioning
confidence: 99%